A 12-month retrospective study of outcomes of COVID-19 drive-through swabbing hubs' screening of asymptomatic population in Qatar - Mohamed G. Al-Kuwari; Mariam A. Abdulmalik; Azza M. Mohammed; Shaikha Abushaikha; Mujeeb C. Kandy (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background There are gaps in understanding the prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among asymptomatic persons in the Middle East including Qatar. The aim of the study was to estimate the point prevalence of Coronavirus disease 2019 (COVID-19), testing positivity rates and risk factors associated with reverse transcription polymerase chain reaction (RT-PCR) positivity among asymptomatic people identified through active population surveillance. # Methods This study was based on a retrospective identification of asymptomatic adults who have not been previously diagnosed with SARS-CoV-2 infection. It includes subjects who were tested using RT-PCR between June 1st , 2020 and May 31st of 2021 at the Primary Health Care Corporation's (PHCC) drive-through testing hubs. The testing data was extracted from the national SARS-CoV-2 PCR database. Sociodemographic characteristics and comorbidities were extracted from the medical records. # Results A total of 148,735 subjects were tested; 5,848 positives, corresponding to a point prevalence of 3.93 (95% confidence interval, CI=3.83-4.03). RT-PCR positivity was higher among women and younger people (30-49 years old; *P*< 0.001). Logistic regression identified age, nationality, chronic comorbidity, and geographical location as significant predictors of asymptomatic infection. The adjusted odds of positive SARS-CoV-2 PCR test were lower among older people, with the odds ratio 0.81 (95% CI=0.75-0.88), and those with multiple chronic conditions 0.87 (95% CI=0.81-0.94). The odds of a positive SARS-CoV-2 were higher among persons from South Asian nationalities . Residents of Central and Western regions had higher odds at 3.37 (95% CI=3.05-3.73) and 1.86 (95% CI=1.68-2.07), respectively. Hypertension (12.8%) and diabetes (12.1%) were the most common comorbidities detected among asymptomatic subjects. # Conclusions Active community testing implemented through the PHCC's drive-through swabbing hubs offers a valuable opportunity to identify asymptomatic COVID-19 cases and reduce the spread of the disease.